Neogene palaeoceanographic changes recorded in a carbonate contourite drift (Santaren Channel, Bahamas). Issue 4 (25th March 2019) - Paulat, Marco; Lüdmann, Thomas; Betzler, Christian; Eberli, Gregor P.
Abstract: The Santaren Drift between the Great Bahama Bank and Cay Sal Bank (Bahamas) is closely linked to the development of the Gulf Stream and its shape and geometry record the local to global oceanographic, climatic and tectonic events since the Miocene. High‐resolution multichannel seismic data from the Santaren Channel allow detailed insight into the growth phases of the contourite drift, and by using the stratigraphic information from Ocean Drilling Program Site 1006 to infer its sedimentation rates. The results bring new understanding to this region and to interpretation of carbonate drifts. The data document that the signatures of a bottom current flow in the Santaren Channel initiated about 12·3 Ma, as indicated by the first occurrence of sheeted drifts and moat development at the northern part of the Santaren Channel. Narrowing and steepening of moat flanks as well as the pronounced upslope migration of the moat reflects a sustained current acceleration of the bottom currents until 5·5 Ma, associated with a transformation into mounded elongated drifts. Between 5·5 Ma and 3·1 Ma, bottom current intensity reached its maximum probably caused by the final closure of the Central American Seaway. The last 3·1 Myr were characterized by a marked increase in volume through flow reaching a maximum during the past 900 kyr. Drift growth was driven by the combined sources of export from the shallow‐water carbonate factory and by pelagic rain. The Middle Miocene channel‐related sheeted drift of the inner Santaren Channel is characterized by low accumulation rates, but a rapid increase of accumulation rates occurred during the Early Pliocene. The contourite drift buildup was disturbed by minor erosional phases with narrow moats in the Late Pliocene due to increasing bottom‐current velocities forced by strengthened Atlantic Ocean ventilation. The Early Pleistocene was dominated by increased periplatform sedimentation and margin progradation facilitated by a reduction in along‐slope current flow speed and a concurrent widening and flattening of the moats.